Implementasi Pendidikan Karakter Siswa Di Kelas Pada Mata Pembelajaran Pendidikan Pancasila Kelas IV Di Sekolah Dasar - Diah Pebriyanti; Irwan Badilla (Elementary Teacher Education Program, Majalengka University, 2023)
Pancasila education is the foundation in building student character. However, the implementation of Pancasila Education has not been comprehensively presented in shaping character. This study aims to determine the implementation of student character education in grade IV Pancasila education subjects in elementary schools and to find out the obstacles faced in implementing character education in grade IV Pancasila education subjects in elementary schools. This type of research is descriptive-qualitative. The data sources in this study are teachers and students. Data collection techniques used include: observation, interviews, and documentation. Data analysis techniques used are data reduction, presentation of verification data. The results of the study suggest that the planning made by the teacher is used as a guide in implementing learning and planting character values. Obstacles in the implementation of learning that include students lacking enthusiasm in learning activities. Thus it is concluded that based on information obtained from teachers and students, the implementation of student character education in Pancasila education subjects at SDN Susukan 01 East Jakarta has been well implemented even though there are still obstacles.